وظيفة الإستفهام المجازي في أحاديث الامام على "ع" الفنية - عربي، موسي; نجاد، سكينة زارع (جامعة بغداد - كلية الآداب, 2017)
Imam Ali word has a high position in Arabic such that has strong effect on people due to having valuable and excellent concepts and meanings. And since Imam Ali prophecy is to guide people from neglect to perfection and to reach this goal, he chose various methods to do his prophecy and used it to induce his words to addressee eg. Arranging his word to figurative interrogation style such that beyond this style, some deep secrets and meanings are hidden. Presence of this style invite people to right and induce their emotions and feelings is among the best presentational style, then it is proper that in order to deep understanding it, one thinks on it based on the speech style and literal and abstract proportion. This study tries to examine figurative interrogation in short anecdotes by Imam Ali in Gorarol hekam and Dorarol hekam and uncover some properties of this style and it's beauties and also rate of this style effect and duty on sending Imam message based on descriptive-analytical method. It is considered that most of the interrogations applied in Imam word doesn't aim to understanding but also, beyond this style some other goals are bidden and often Imam Ali has used interrogation style in religious purposes such as guiding people and advicing them and paying attention to their actions and also blaming them due to materialism and ignoring hereafter day.
تحتل أحاديث الإمام علي (عليه السلام) الفنية مكانة عالية في الأدب العربي إذ تترك على المتلقي تأثيرا بالغا لما فيها من مفاهيم ومعان رفيعة قيمة، وبما أن رسالة الإمام علي (عليه السلام) كانت هداية الناس من الجهل والضلالة إلى النور والهداية استعمل شتى الأساليب لإلقاء كلامه على المتلقي، ومنها توظيف الاستفهام المجازي في كلامه إذ تكمن ورائه رموز ومفاهيم عميقة، ليثير بها مشاعر الجمهور وعواطفهم، فيعتبر من أروع أساليب الإنشاء لذا من الواجب الوقوف عليه لفهمه على أساس القرائن اللفظية والمعنوية وسياق الكلام؛ وضم البحث دراسة وظائف الاستفهام المجازي في أحاديث الإمام علي (عليه السلام) القصار بـــــــ (كتاب غرر الحكم ودرر الكلم)؛ محاولة للكشف عن ميزاته وجمالياته ووظيفته لإيصال رسالة الإمام (عليه لسلام)، ومدى تأثيره في المتلقي، وذلك على أساس المنهج الوصفي -التحليلي، ومن الملاحظ فإن أكثر الاستفهامات الواردة في كلام الإمام (عليه السلام) ليس غرضه طلب الفهم بل كمن وراءه غرض آخر، فالإمام (عليه السلام) استعمل أسلوب الاستفهام غالبا في غرض ديني كإرشاد الناس ووعظهم وانتباههم لأعمالهم وتوبيخ الناس لاهتمامهم بالدنيا وحبها وغفلتهم عن الآخرة.
Keywords: الاستفهام المجازي -- على بن ابى طالب، خليفة المسلمين -- الدلالات اللغوية -- المذهب الشيعى